Theoretical study of the double ionization of the He isoelectronic sequence by protons and antiprotons - López, Sebastián David (2012)
We evaluate the fully differential cross sections (FDCS) for the double ionization of the He-isoelectronic sequence by proton and antiproton impact. We use a distorted wave model recently introduced by the authors based on static and dynamically screened charges for the final continuum state. We identify three main collision mechanisms, which we denote as: back-to-back, recoil and binary emissions. We discuss the relative relevance in the FDCS of these mechanisms as the electron emission energies and nuclear charges are varied. We study the variation of the electronic angular distributions according to well established scaling rules for the electron momenta and energies. The dependence of the FDCS on the projectile charge sign is analyzed and found to become more relevant for increasing nuclear charges of the target.